The effect of soil microplastics on Oryza sativa L. root growth traits under alien plant invasion - Li, Guanlin; Zhao, Xiaoxun; Iqbal, Babar; Zhao, Xin; Liu, Jingjing; Javed, Qaiser; Du, Daolin (Frontiers in Ecology and Evolution, 2023)
Invasive alien plants pose severe threats to agroecosystems. Microplastic (MP) contamination in farmland soil is also concerning, as it causes crop stress and reduces productivity. However, the effects of the interactions between invasive alien plants and MP in the soil impact crops remain unclear. Herein, belowground plant characteristics associated with stress responses were examined in a pot experiment using root scan analyzes of rice plants exposed to Solidago canadensis L. invasion, polyethylene MP contamination, and a combined treatment. The observed changes in root growth traits under Canada goldenrod (Solidago canadensis L.) invasion were the least adverse, whereas S. canadensis invasion combined with soil MP contamination had the most adverse effects on root growth. Solidago canadensis L. invasion increased all belowground indices except root height and mean root diameter, which was upregulated in the soil MP contamination treatment. The combined treatment (S. canadensis invasion and soil MP contamination) reduced the belowground root growth traits more than the other treatments. The root growth traits may have been affected by changes in the antioxidant enzyme activity of the roots caused by the treatments. The combined effects of S. canadensis invasion and MP toxicity on rice root growth traits raise concerns regarding potential yields, financial damage, and consequences related to a potential move into the food web.